The risks you can’t foresee: what to do when there’s no playbook - Kaplan, RS; Leonard, HBD; Mikes, A (Harvard Business School Publishing, 2020)
No matter how good their risk management systems are, companies can’t plan for everything. Some risks are outside people’s realm of experience or so remote no one could have imagined them. Some result from a perfect storm of coinciding breakdowns, and some materialize very rapidly and on an enormous scale. These novel risks, as the authors call them, cannot be addressed by following a standard playbook. This article describes how to detect the emergence of a novel risk (start by looking for anomalies and appointing “chief worry officers”) and then how to mobilize resources to mitigate its impact, deploying a critical incident team or empowering local personnel to tackle it.